2007
DOI: 10.1111/j.1365-2133.2007.07970.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipomas after blunt soft tissue trauma: are they real? Analysis of 31 cases

Abstract: The existence of a pathogenic link between blunt soft tissue trauma and the formation of post-traumatic lipomas is still controversial. Two potential mechanisms are discussed. Firstly, the formation of so-called post-traumatic 'pseudolipomas' may result from a prolapse of adipose tissue through fascia induced by direct impact. Alternatively, lipoma formation may be explained as a result of preadipocyte differentiation and proliferation mediated by cytokine release following soft tissue damage after blunt traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 18 publications
3
72
1
1
Order By: Relevance
“…However, several authors have not been able to identify anatomical confirmation for the hypothesis of deep fascial injury leading to the development of PTL [2,4]. In this case presentation, the patient was not obese and the development of de novo adipose tissue in the ventral lower thorax/upper abdominal region favors the theories postulated by Galea et al in 2009 [5].…”
Section: Figure 3: (A) Plain T2w Mri Axial Image Of Abdomen Demonstrasupporting
confidence: 54%
“…However, several authors have not been able to identify anatomical confirmation for the hypothesis of deep fascial injury leading to the development of PTL [2,4]. In this case presentation, the patient was not obese and the development of de novo adipose tissue in the ventral lower thorax/upper abdominal region favors the theories postulated by Galea et al in 2009 [5].…”
Section: Figure 3: (A) Plain T2w Mri Axial Image Of Abdomen Demonstrasupporting
confidence: 54%
“…It is most commonly associated with translocations and rearrangements of the 12q13~q15 chromosomal region [9]. A competing theory which was proposed for lipoma following trauma revealed that growth factors, cytokines, and other inflammatory mediators which are released following blunt trauma to soft tissue, induce preadipocyte differentiation into mature adipocytes and form a clinically apparent mass [10].…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde travma sonucu 17 yaşında adölesanda ya da infantil dönemde gelişen vulvar lipom vakaları da bildirilmiştir [3,6]. Klinik prezentasyonları mobil, ağrısız, yavaş büyüyen, tek ya da çoklu sayıda olabilen ve diğer organların serozasına kadar uzanacak şekilde derin yerleşim gösterebilen kitleler şeklindedir [7,8]. Literatür incelendiğinde bizim sunduğumuz vakadan farklı olarak büyük boyutlara ulaşan lipomların, ekzofitik olduğu görülmüştür [9,10].…”
Section: Discussionunclassified